2016
DOI: 10.1115/1.4032205
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of the Flow in a Low-Pressure Industrial Steam Turbine With Part-Span Connectors

Abstract: An experimental and numerical study on the flow in a three-stage low-pressure (LP) industrial steam turbine is presented and analyzed. The investigated LP section features conical friction bolts in the last and a lacing wire in the penultimate rotor blade row. These part-span connectors (PSC) allow safe turbine operation over an extremely wide range and even in blade resonance condition. However, additional losses are generated which affect the performance of the turbine. In order to capture the impact of PSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Traupel 15 ) are normally used to determine the efficiency losses. More detailed numerical and experimental studies on the flow impact of part-span connectors in LP steam turbine blading have recently been published by Ha¨fele et al [16][17][18] Depending on the size and position of the elements, an efficiency decrease of several percentage points must be expected. 17…”
Section: Damping Elements Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Traupel 15 ) are normally used to determine the efficiency losses. More detailed numerical and experimental studies on the flow impact of part-span connectors in LP steam turbine blading have recently been published by Ha¨fele et al [16][17][18] Depending on the size and position of the elements, an efficiency decrease of several percentage points must be expected. 17…”
Section: Damping Elements Developmentmentioning
confidence: 99%
“…The test rig setup is shown in Figure 2. Further details can be found in Ha¨fele et al [16][17][18] The turbine is equipped with various temperature and pressure probes for a complete thermodynamic evaluation. Moreover, strain gauges are applied to several moving blades of the rows.…”
Section: Test Rigmentioning
confidence: 99%
“…Here, O-grids around blades and PSC profiles are used. Further details can be found in Ha¨fele et al 1,2 In order to perform a study on the aerodynamic effects of geometrical variations of PSCs using hexahedral meshes, the CAD model and meshing procedure which have been formerly used need to be adjusted. Because of the time-consuming grid generation, it is inconvenient to create a new mesh for every single PSC configuration.…”
Section: Parameterization and Grid Generationmentioning
confidence: 99%
“…The impact of PSCs on aero-thermodynamics in wet steam flow has been studied by Ha¨fele et al 1 and details of the hexahedral mesh-generation for LP blades with PSC are shown in Ha¨fele et al 2 These former numerical investigations showed the complexity of the three-dimensional (3D) flow field in LP stages with PSCs mounted between rotor blades. Furthermore, the blockage of the steam flow due to the PSC within the blade channel and related blade design aspects have been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases boundary conditions are based above all on measurements of experimental steam turbines, e.g. [7].…”
Section: Introductionmentioning
confidence: 99%